If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (15x + -4x) + -1(10 + -1x) = 0 Combine like terms: 15x + -4x = 11x (11x) + -1(10 + -1x) = 0 (11x) + -1(10 + -1x) = 0 (11x) + (10 * -1 + -1x * -1) = 0 (11x) + (-10 + 1x) = 0 Reorder the terms: -10 + (11x) + 1x = 0 Combine like terms: (11x) + 1x = 12x -10 + 12x = 0 Solving -10 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 12x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 12x = 0 + 10 12x = 0 + 10 Combine like terms: 0 + 10 = 10 12x = 10 Divide each side by '12'. x = 0.8333333333 Simplifying x = 0.8333333333
| 35y+6=61 | | 6x-2x-5=6+21 | | a/3+3=9 | | 63-4x=12-9x | | 9x-6x-5x+6= | | 5x+6=54 | | 8-(4x-1)=1-5x | | 33=-4(7k-6) | | 1+10-5a= | | -6(y-1)=2y+7-y+4 | | cost=.35 | | 3(12)+5y=20 | | -3x-5=-4 | | 3x-2=x+3 | | -5x-8=-4 | | 10x-158=3x-11 | | y(x-1)-4(x-1)= | | 7[m+9]=-2[m-5]+2 | | 3(5x+11)=-42 | | 3(x+2)-2x+4=x+5 | | (8x-18)+(7x-31)=(13x-9)+(19x-6) | | 12z-9-10z+3-8=z-9+3z+10-10z | | 8x+2x-3x-2x= | | 8x+1=23 | | 5m-10n=2 | | 3a+6b+3c= | | 8x=10+x | | -n-2u=5-n | | 9x+14=-40 | | 15x-3y=-18 | | n/7=12/42 | | -5X-7Y=-70solvey |